A transition programme to enhance ICU new graduate nurses' professional identity and intention to remain employed: A pre‐ and postevaluation - Fen Hu; Xin‐Bo Ding; Ru‐Han Zhang; Su‐Yun Li; Rui Cao; Lan Deng; Jin Li; Xing Fu; Xiao‐Ping Zhu; Jie Chen (Wiley, 2023)
Abstract Aims To investigate the effect of a transition programme including cognitive‐behaviour‐based preceptorship intervention on ICU new graduate nurses' (NGNs)' professional identity and their intention to remain employed. Design One‐arm pre‐ and post‐test design followed the TREND Statement. Methods NGNs' professional identity and intention to remain employed were measured at baseline (T1), postintervention (1 month, T2) and 6‐month follow‐up (T3). Results Fifty‐three NGNs completed the programme, and their professional identity score significantly increased postintervention [from 111.5 (SD = 16.72) at T1 to 114.2 (SD = 9.12) at T2, p < 0.05], but decreased at T3 [105.8 (SD = 9.44) compared with T1 and T2, p < 0.05]. There was no significant difference in ICU NGNs' intention of remain employed outcomes at three time points (p > 0.05). The transition programme was effective to improve ICU NGNs' professional identity immediately after the intervention, but the increment did not maintain at the 6‐month follow‐up.